Pironetin reacts covalently with cysteine-316 of α-tubulin to destabilize microtubule - Jianhong Yang (Nature Portfolio, 2016)
Microtubule assembly and disassembly is the target of many anticancer therapies, with β-tubulin the most-frequent target. Here, the authors used biochemical and biophysical techniques to demonstrate pironetin binds to α-tubulin and thereby inhibits microtubule polymerization providing a basis for the rational design of novel anticancer drugs.